Dampak Objek Wisata Patung Tuhan Yesus Terhadap Kehidupan Sosial Ekonomi Masyarakat Buntu Burake Kabupaten Tana Toraja - Bai’ru, Frelia Natali Refi; Charles Kapile (Jurusan Pendidikan IPS, Fakultas Keguruan dan Ilmu Pendidikan Universitas Tadulako, 2021)
This study aims to describe (1) the Socio-Economic Conditions of the Community in the surrounding Attractions Statue of the Lord Jesus Buntu Burake, (2) the Impact of the Attractions Statue of the Lord Jesus against the socio-economic conditions of communities around Buntu Burake of Tana Toraja. The subject in this research is the Branch of Attractions, Parking, and Traders. The research method used a descriptive method with a qualitative approach. Data collection techniques through observation, interviews, and documentation. The results of this study showed that the socio-economic conditions of people with its attractions, namely the community were originally only worked as a fuckin buildings, housewives, farmers and some even do not have a job or unemployment. With its attractions then provide enormous opportunities for the community to plunge into the tourism sector, they are working as the manager's Attractions, a Parking Attendant, and some work as sellers/traders, then they automatically earn income. The income that is produced by that is if the attraction is visited then the income of the community of about 200.000-600.000 and if the object of its empty then the income of the community of about 100.000-Rp300.000. Attractions Statue of the Lord Jesus has given impact on the socio-economic conditions of communities around Buntu Burake such as create jobs, increasing incomes and also the government, and the impact on development.